Overexpression of S100A4 as a biomarker of metastasis and recurrence in oral squamous cell carcinoma - Jayalakshmi NATARAJAN; Keith HUNTER; Vimi S MUTALIK; Raghu RADHAKRISHNAN (University of São Paulo, 2014)
S100A4, a biomarker of epithelial mesenchymal transition (EMT), plays an important role in invasion and metastasis by promoting cancer cell motility. In oral squamous cell carcinoma (OSCC), metastasis results in 90% of cancer associated mortality. Objective: To investigate the role of S100A4 expression as an important component of the epithelial mesenchymal transition (EMT) program in oral squamous cell carcinoma (OSCC). Material and Methods: S100A4 protein expression was assessed semi-quantitatively by immunohistochemistry in 47 histologically confirmed cases of oral squamous cell carcinoma (OSCC) and 10 normal oral mucosal biopsies. The association between the S100A4 overexpression and the aggressive features of OSCC were analyzed by X2 test. Results: Moderate to strong cytoplasmic expression of S100A4 was observed in 30 out of 47 specimens of OSCC (64%). Overexpression of S100A4 was significantly associated with the clinical stage, lymph node involvement, metastases, pattern of invasion and recurrence (p<0.05). Conclusion: S100A4 expression represents an important biomarker of prognostic significance that may be used to identify a subset of patients at high risk of invasion and metast